Influence of elemental impurities in aluminum hydroxide adjuvant on the stability of inactivated Japanese Encephalitis vaccine, IXIARO®. Issue 44 (4th November 2015) - Schlegl, Robert; Weber, Michael; Wruss, Jürgen; Low, Donald; Queen, Kirsten; Stilwell, Shaun; Lindblad, Erik B.; Möhlen, Michael
Abstract: Aluminum hydroxide is a critical raw material in the production of many vaccines. It is used as an adjuvant in the formulation of the final bulk vaccine, and for this it must meet the specifications of the European Pharmacopeia Monograph. We investigated whether vaccine stability was affected by the presence of trace amounts of elemental impurities in commercially available aluminum hydroxide. The content of residual elemental impurities in commercially available aluminum hydroxide was determined by selective and sensitive inductively coupled-plasma mass spectrometry and inductively coupled plasma atomic emission spectroscopy. We found significant differences between different suppliers, but also between different lots from the same supplier. Inactivated Japanese encephalitis vaccine, IXIARO ®, was used to study the effect of residual metals in aluminum hydroxide on antigen stability. We propose that antigen degradation occurred via a pathway involving the metal-catalyzed, auto-oxidation of a process-related impurity (sulfite). Thus, sulfite auto-oxidation resulted in antigen degradation when residual Cu was present at elevated concentrations in aluminum hydroxide.